2014
DOI: 10.1037/cpp0000052
|View full text |Cite
|
Sign up to set email alerts
|

Integration of electronic patient-reported outcomes (ePROs) into pediatric clinic settings across hematology/oncology/bone marrow transplant.

Abstract: Despite the benefits of patient reported outcomes (PROs), the systematic use of PRO assessment in clinical care is rare. The goal of this pilot project was to examine the feasibility of PRO assessment via the Patient Reported Outcomes Measurement Information System-Computerized Adaptive Testing (PROMIS-CAT) within pediatric hematology, oncology, and bone marrow transplant (BMT) clinic settings. Fifty-one patients (ages 5 to 26 years), 53 parents, and 13 medical providers were recruited successfully. After pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…A number of observational and randomized controlled trials have shown clear benefits to routine HRQOL monitoring . The time needed for our participants to complete each HRQOL measure was comparable to that previously published for acquiring PROMIS ® data . Given our experience, it is worth noting that the digital platform used for data collection and Wi‐Fi access could affect the feasibility of completing the PROMIS‐CAT assessments electronically in the clinic setting.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A number of observational and randomized controlled trials have shown clear benefits to routine HRQOL monitoring . The time needed for our participants to complete each HRQOL measure was comparable to that previously published for acquiring PROMIS ® data . Given our experience, it is worth noting that the digital platform used for data collection and Wi‐Fi access could affect the feasibility of completing the PROMIS‐CAT assessments electronically in the clinic setting.…”
Section: Discussionsupporting
confidence: 91%
“…23 Moreover, symptoms reported by pediatric cancer patients were more accurately detected using HRQOL measures in the outpatient setting, compared with standard clinician interviews. 24 Myrvik et al 25 found the electronic measurement of HRQOL in the pediatric outpatient setting to be feasible, including hematology, oncology, and stem cell transplant (SCT) clinics; however, the study included only a small number of patients with SCD. The feasibility of Internet-based electronic assessment of HRQOL measures using tablets as part of the routine care in sickle cell clinics while maintaining workflow has not been well established.…”
mentioning
confidence: 99%
“…While provider acceptability of PROs has varied by medical discipline and across types of care (Myrvik, 2013; Stover et al, 2015), provider acceptability in clinical HIV care is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study in pediatric sickle cell, oncology, and bone marrow transplant patients confirmed the feasibility of obtaining electronic PROs in the pediatric clinic setting. 29 Electronic PROs were captured on tablets in the clinic waiting room and the results of the PROs were provided to the clinicians during the visit. Cincinnati Children's Hospital has adopted a tablet and kiosk-based system to collect PROs in their outpatient clinics under an initiative to improve quality of care, demonstrating feasibility within a large pediatric healthcare system and diverse patient populations.…”
Section: Pro Use Improves Physician Patient Communicationmentioning
confidence: 99%